Menakar Dampak Fenomena Pandemi Covid-19 Terhadap Perbankan Syariah - S Sumadi (Prodi Hukum Ekonomi Syariah Fakultas Agama Islam, Universitas Muhammadiyah Purwokerto, 2020)
Covid-19 has had a significant impact on world economic development. The Covid-19 pandemic is a challenge for the business world, including the banking financial services industry. This causes our financial system to be eroded, including the interest in conventional banks. This study was conducted to determine how the operational strategy management carried out by Islamic Banking in carrying out its function as a banking intermediary institution, namely in terms of raising funds and channeling funds carrying out their duties and functions in the midst of the Covid-19 pandemic, as well as to what extent Islamic Banking can carry out its intermediation function. This research is a type of qualitative research with a naturalistic research method approach because the research is carried out in natural conditions. The discussion was carried out with descriptive analysis. The results showed the impact of the Covid-19 pandemic on the banking intermediation function, based on the results of a study at Bank Syariah Mandiri, namely Financing and TPF, the Bank showed a fluctuation. On the financing side, Bank Syariah Mandiri from January to March 2020 tends to increase. On the side of the collection of funds (DPK), Bank Mandiri Syariah shows fluctuation. The impact of the Covid-19 Pandemic on the management of banking operational strategies. Based on the results of a study at Bank Syariah Mandiri shows that: First, all banks implement economic stimulus related to restructuring financing for customers affected by the Covid-19 pandemic based on POJK No.11 / POJK.03 / 2020. Second, the development of digital mobile banking applications for banks Sharia.